The basic regularities of multicomponent rectification in the mode of the first class fractionalization - L. A. Serafimov; K. Yu. Tarkhov (Тонкие химические технологии, 2010)
The basic regularities and some peculiarities of multicomponent mixtures rectification in the mode of the first class fractionalization are considered. Rectification trajectories are presented for ternary zeotropic mixtures for the case when the composition of initial mixture belongs to the α=1 manifold.